Case report: Muscle involvement in a Chinese patient with TRNT1-related disorder - Wei, Cui-Jie; Liu, Yi-Dan; Yang, Yan-Ling; Wu, Yuan; Liu, Jie-Yu; Chang, Xing-Zhi; Hua, Ying; Liu, Yu-He; Xiong, Hui (Frontiers in Pediatrics, 2023)
The TRNT1 gene encodes tRNA nucleotidyltransferase 1, which catalyzes the addition of cytosine-cytosine-adenosine (CCA) to the ends of cytoplasmic and mitochondrial tRNAs. The most common clinical phenotype associated with TRNT1 is autosomal recessive sideroblastic anemia with B-cell immunodeficiency, periodic fever, and developmental delay (SIFD). Muscle involvement has rarely been reported in TRNT1-related disorders. Here we report a Chinese patient with incomplete SIFD and hyperCKemia, and explored the skeletal muscle pathological changes. The patient was a 3-year-old boy with sensorineural hearing loss, sideroblastic anemia, and developmental delay since infancy. At the age of 11 months, significantly increased levels of creatine kinase were noted, accompanied by mild muscle weakness. Whole-exome sequencing revealed compound heterozygous variants of the TRNT1 gene, c.443C>T (p.Ala148Val) and c.692C>G (p.Ala231Gly), in the patient. Western blot showed a decreased expression of TRNT1 and cytochrome c oxidase subunit IV (COX IV) in the skeletal muscle of the patient. Electron microscopy observation of skeletal muscle pathology revealed abnormal mitochondria of various sizes and shapes, supporting a diagnosis of mitochondrial myopathy. The present case indicates that in addition to the classic SIFD phenotype, TRNT1 mutations can cause mitochondrial myopathy, a rare clinical phenotype of TRNT1-related disorders.